Nimotuzumab combined with radiotherapy+/- chemotherapy for definitive treatment of locally advanced squamous cell carcinoma of head and neck: a metanalysis of randomized controlled trials - Guan, Meng; Zhang, Dan; Zhao, Yue; Mao, Mingdi; Shen, Kang; Wang, Xia; Bi, Chun (Frontiers in Oncology, 2024)
Objectives: To assess the efficacy and safety of nimotuzumab in combination with radiotherapy or chemoradiotherapy for locally advanced head and neck squamous cell carcinoma. Methods: Systematic searches were performed on PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure, China Biomedical Medicine, Wanfang, VIP databases. Seven eligible randomized controlled trials (n = 1012) were selected through rigorous inclusion and exclusion criteria. Results: A total of 1012 cases were included. including 508 (50.2%) in the nimotuzumab combination treatment group; There were 504 cases (49.8%) in the control group. The results of meta-analysis showed that the overall survival (Hazard Ratio [HR]=0.75, 95% Confidence Interval [CI]: 0.62-0.90, P<0.05), progression-free survival (HR=0.69, 95% CI: 0.54-0.87, P<0.05), complete response rate (Risk Ratio [RR]=1.52, 95% CI: 1.24-1.86, P<0.05), and objective response rate (RR=1.32, 95% CI: 1.17-1.48, P<0.05) were significantly improved in the nimotuzumab combination treatment group compared with the control group. In terms of the incidence of adverse effects, only the incidence of rash was the nimotuzumab combination group higher than in the treatment alone group, and there was no significant difference between the remaining adverse reactions (neutropenia, anemia, nausea/vomiting, mucositis, dermatitis, dysphagia). Conclusions: Nimotuzumab combined with radiotherapy or chemoradiotherapy is more effective than radiotherapy alone or chemoradiotherapy in locally advanced squamous cell carcinoma of the head and neck, and the safety profile is controllable. Therefore, the addition of nimotuzumab to treatment is expected to be an effective treatment option for this disease. However, more prospective randomized controlled trials are needed to fully explore the effectiveness of this treatment in patients with locally advanced head and neck squamous cell carcinoma.